Development of nanoemulsion CO2 absorbents for mass transfer performance enhancement. (May 2018) - Kim, Seonggon; Jeong, Myunghwan; Lee, Jae Won; Kim, Sae Young; Choi, Chang Kyoung; Kang, Yong Tae
Abstract: Nanofluids as CO2 absorbents have problems involving precipitation or flocculation of the seeding particles. Nanoemulsion CO2 absorbents are expected to solve these problems. In this study, nanoemulsion (Dodecane/Methanol) absorbents were proposed and their thermophysical properties and dispersion characteristics were evaluated for mass transfer performance enhancement during CO2 absorption process. Both Span 60 and Tween 60 were selected due to their nonionic surfactant feature and hydrocarbon chemical types of dodecane. The nanoemulsion absorbents were ultrasonically manufactured after adding Span 60 and Tween 60 in a ratio of 4:6 to match the required hydrophile-lipophile balance (HLB = 11). Thermal conductivity and viscosity of nanoemulsion absorbents were measured for various surfactant ratios. Tyndall effects and turbidity measurements were executed to find out the best dispersion stability condition. An optimal ultrasonication time was proposed based on the smallest mean size of nanoemulsion droplets and their uniformity. Both mechanisms of thermophysical properties and dispersion stability of nanoemulsion absorbents were proposed based on cryo transmission electron microscope (TEM) results.